Development of Batik Motifs using Symatrig Application to enhance productivity and competitiveness of SMEs - Dinda Kartika; Debi Yandra Niska; Fevi Rahmawati Suwanto; Sisti Nadia Amalia; Nurhasanah Siregar; Anita Talia; Fikri Syahputra (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2025)
The Village Development Index (IDM) of the North Padang Lawas Regency in 2023 remained underdeveloped. The status has been upheld since 2018, although many craft and tourism industries in North Padang Lawas Regency have the potential to contribute to the regional economy, one of which is batik small medium enterprises (SMEs). Batik SMEs in North Padang Lawas Regency are predicted to be the featured product of the regency. One of the batik SMEs, i.e., Batik Sekar Najogi, becomes the icon of North Padang Lawas Regency. However, limited knowledge and resources in developing varied batik motifs have made the batik SMEs in this regency unpopular, both provincial and national. The Abdimas Team and partners, i.e., the Department of Industry and Trade of North Padang Lawas Regency, hold training and coaching for the Symatrig computer application to develop batik motifs based on symmetrical patterns in mathematics. The application also has different motif development patterns to produce various batik motifs. Of 30 batik makers joining the training, 13 agree to utilize the Symatrig application in their businesses, while the others strongly agree. Batik makers also offer recommendations to continue conducting such activity to support those involved in the industry.